Are there ethics in sales profession – A study (International Journal of Scientific Research and Management (IJSRM), 2016)
Sales management is an integral part of marketing process. Sales’ being an essential component of promotion has evolved overtime and is deeply influenced by the evolution in the society and market place. Historically sales profession has always been perceived as being dishonest and unethical. There have been, in recent times there has asurge in the ethical issues related to sale. This paper attempts to look at some of the ethical issues related to sales from the sales professionals’ perspective.